The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12917-017-1124-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving sperm banking efficiency in endangered species through the use of a sperm selection method in brown bear (Ursus arctos) thawed sperm

Abstract: BackgroundSperm selection methods such as Single Layer Centrifugation (SLC) have been demonstrated to be a useful tool to improve the quality of sperm samples and therefore to increase the efficiency of other artificial reproductive techniques in several species. This procedure could help to improve the quality of genetic resource banks, which is essential for endangered species. In contrast, these sperm selection methods are optimized and focused on farm animals, where the recovery task is not as important as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
10
0
2
Order By: Relevance
“…In effect, in the horse, the seminal protein CRISP3 has been found to inhibit the binding mechanism between viable spermatozoa and PMN involved in phagocytosis [ 52 ], improving fertility in mares [ 53 ]. In jennies, suppression of sperm-PMN binding by the presence of seminal plasma has also been identified [ 18 ], which would also be in agreement with the observed effect of seminal plasma in this study. We can thus hypothesize that sperm selection with Equicoll leads to the removal of seminal plasma components involved in the sperm protection from phagocytosis, since a previous study reported that the percentages of phagocytosis are low in the presence of seminal plasma [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In effect, in the horse, the seminal protein CRISP3 has been found to inhibit the binding mechanism between viable spermatozoa and PMN involved in phagocytosis [ 52 ], improving fertility in mares [ 53 ]. In jennies, suppression of sperm-PMN binding by the presence of seminal plasma has also been identified [ 18 ], which would also be in agreement with the observed effect of seminal plasma in this study. We can thus hypothesize that sperm selection with Equicoll leads to the removal of seminal plasma components involved in the sperm protection from phagocytosis, since a previous study reported that the percentages of phagocytosis are low in the presence of seminal plasma [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Also in pigs, centrifugation of semen with SLC with Porcicoll prior to cryopreservation increases the cryotolerance and fertilizing ability of frozen/thawed sperm [ 19 , 20 ]. Even in brown bears, centrifugation with SLC has also been reported to improve the proportion of spermatozoa with intact plasma membrane and acrosome [ 17 , 18 ]. In bulls, centrifugation through SLC with a species-specific colloid (Androcoll-B/Bovicoll) also results in an increase in the proportions of spermatozoa with high mitochondrial membrane potential and high relative levels of peroxides [ 16 ], and in some kinematic parameters, but has no impact upon total and progressive motility of cooled-stored semen [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have been carried out in this direction. It was found that SLC positively influenced some of the semen parameters in species and breeds such as great panda (Cai et al, 2018), brown bear (Álvarez‐Rodríguez et al, 2016; Anel‐Lopez et al, 2017), camel (Malo, Crichton, Morrell, Pukazhenthi, & Skidmore, 2017), misty panther (Tipkantha et al, 2016), andalusian donkey (Ortiz et al, 2015), red deer (Anel‐López et al, 2015) or blanca‐celtibérica goat (Jiménez‐Rabadán et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…SLC has been successfully used to select sperm of stallions (Hoogewijs et al, 2011) prior to cryopreservation and remove bacteria from ejaculates in boar semen (Morrell & Wallgren, 2011). SLC has also been tested on many wild animal species, such as giant panda (Cai et al, 2018), brown bear (Anel‐Lopez et al, 2017) and clouded leopard (Tipkantha, Thuwanut, Morrell, Comizzoli, & Chatdarong, 2016). Despite its wide application, there are relatively few publications on the influence of the SLC method carried out before freezing on the quality of bull sperm, which is analysed by kinematic and morphological parameters on thawed semen.…”
Section: Introductionmentioning
confidence: 99%